(3ERgGb GdMb aj QO THgI GdaQbI GdhgGHjIs - (3GdgeOGfj, GdcGXej, eMeO Hf YHO GdhgGH Hf OGhO, J (B1303(3g`s ((3eMeO GdfLa CHGOjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQM UOhQfG HCSQGQ cJGHg(B... (3CeG HYO(B... (3bO YKQJ CjGe EbGeJj aj HZOGO Ydi hQjbGJ deMeO Hf YHO GdhgGH GdMLGRj EeGe GdaQbI GdhgGHjI(B...s
(3BNQgG (B:s
(3hGdKGfjI bhdg JYGdi(B: (3Pdc HCfge GSJMHhG GdMjGI GdOfjG Ydi GdBNQI(B. (3aUQM HCf GdcaQ (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds